เกณฑ์ในการประเมินคุณภาพรายการเด็กทางโทรทัศน์ - มนัสวินี จันทะเลิศ (จุฬาลงกรณ์มหาวิทยาลัย, 2005)
This qualitative research attempts to investigate the criteria for quality assessment in children television program. The purpose of the study is to analyze principles that subjects used as the criteria for quality assessment in children television program and seek out the similarity and difference of those criteria. The subjects were divided into three groups: government, social institutions, producers of children television program. Regarding the first groups of subjects, documents relation to children television program of government and social institutions were selected for the sample of the study, while the In-depth interview was applied to collect data from the producers. The study found the criteria for quality assessment of three groups of subjects as follow; government has emphasized on education and knowledge, social values, and religious and moral, respectively. For the social institutions, the combination of knowledge and entertainment has been crucially underlined following by the development of thinking system, and social harmonization. The producers of children television program has focused on interest and need of each level of children, and variety of content and format of the program. For the similarity, all assessors have determined that the most importance feature of children TV program is to deliver the necessary knowledge which is appropriate for each age of children. Furthermore, the social institutions has mentioned that Thai cultural promotion is required whereas the producers of children television program has suggested that presentation technique is also essential to attract children’s attention. Nevertheless, it is not apparently found the different criteria among three assessors.